Water power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Rural electrification, integrated water management and small-scale hydropower are the main subjects for discussion at the Hydro Africa 2003 conference, to be held in Arusha, Tanzania, 17 19 November 2003, by the International Centre for Hydropower...